Theory of small reflections for conjugately characteristic-impedance transmission lines - Torrungrueng, Danai; Thimaporn, C.; Lamultree, S.; Krairiksh, M. (My University, 2008)
In this letter, the standard theory of small reflections (TSR) is generalized for the case of multi-section transformers, composed of conjugately- characteristic-impedance transmission lines (CCITLs) connected in cascade, with small discontinuities. Using the assumption of small reflections, the total voltage reflection coefficient looking into the input of the transformer can be approximated, resulting in the TSR for multi-section CCITL transformers with small discontinuities. Numerical results, some physical interpretations and potential applications of results will be discussed in this letter. © 2008 IEEE.
Keywords: Conjugately characteristic-impedance transmission lines (CCITLs); Theory of small reflections (TSR)